Invitation to Write Book Reviews and Library Research - Joel Rey Ugsang Acob; Sahrir Sillehu (Alliance of Health Activists (AloHA), 2021)
EDITORIAL We need to inform you again that the Aloha International Journal of Multidisciplinary Advancement (AIJMU) has a mission to publish research results and ideas from various disciplines of science and technology. In this editorial, we constantly invite researchers and academics around the world to share their best papers in this journal. In April 2021, we invite authors to publish scientific papers which are a form of document study. In this case, we can accept articles from document studies in short form such as book reviews, but we also look forward to the presence of articles and long forms, such as library research. Book review is a type of short paper (usually contains 1000 to 200 words), which contains a review of a book that the author considers interesting or important. In addition to the title, author and affiliation, this article consists of at least 4 important parts, namely an introduction, a review (a summary of the book's contents, strengths, weaknesses and suggestions if any), conclusions and references. However, authors may write in a different systematics as long as they do not go outside the principles of writing a book review. Meanwhile, library research is one type of qualitative research that emphasizes data sources in the form of documents, although it can be strengthened by other data sources, for example the results of interviews. This type of paper is usually written in a large number of words, for example 4000 to 10000 words, depending on the rules of the journal. There are three main types of literature research: historical studies, biographical studies and document studies. We hope that articles based on document studies will further enrich the database of scientific papers in this journal, which in turn can contribute to the development and advancement of science and technology.